2017
DOI: 10.1002/2016ja023516
|View full text |Cite
|
Sign up to set email alerts
|

Statistical analysis of the reflection of incident O+ pickup ions at Mars: MAVEN observations

Abstract: Analyzing ~1.3 year data set of O+ ion velocity distribution functions obtained from the Suprathermal and Thermal Ion Composition instrument on the Mars Atmosphere and Volatile Evolution (MAVEN) spacecraft, we statistically investigate reflections of incident O+ pickup ions (>10 keV) occurring below the Martian bow shock. To quantitatively evaluate importance of the reflection of incident O+ pickup ions, we estimate reflection ratios by calculating average inward and outward O+ ion fluxes above the Martian bow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…However, the lack of energetic neutral oxygen flux over the sensitivity level of the energetic neutral particle instruments on MEX suggests that the sputtering rate may be lower than theoretical predictions (Futaana et al, ). It is also currently unclear how the sputtering estimates under a primordial solar wind conform to the strong dependence of pickup O + reflection ratios on p dyn (caused by stronger magnetic fields/smaller gyroradii in the sheath) recently reported by Masunaga et al ().…”
Section: Discussionmentioning
confidence: 88%
“…However, the lack of energetic neutral oxygen flux over the sensitivity level of the energetic neutral particle instruments on MEX suggests that the sputtering rate may be lower than theoretical predictions (Futaana et al, ). It is also currently unclear how the sputtering estimates under a primordial solar wind conform to the strong dependence of pickup O + reflection ratios on p dyn (caused by stronger magnetic fields/smaller gyroradii in the sheath) recently reported by Masunaga et al ().…”
Section: Discussionmentioning
confidence: 88%
“…Numerical simulations have predicted this hemispheric asymmetry of precipitating ions along the solar wind electric field (e.g., Chaufray et al, ; Curry et al, ; Fang et al, ; Luhmann & Kozyra, ). Recently, such a hemispheric asymmetry of precipitating ion fluxes with respect to the direction of the upstream solar wind electric field was observationally confirmed by MAVEN (e.g., Brain et al, ; Hara, Luhmann, et al, ; Masunaga et al, ).…”
Section: Introductionmentioning
confidence: 81%
“…One of the major sputter sources at Mars are incident O + pick up ions that were ionized by the solar wind but re-entered the Martian atmosphere (e.g., . Masunaga et al (2017) found that the rate of O + that do not re-enter the Martian atmosphere is strongly dependent on IMF, solar wind dynamic pressure and the gyroradius of the O + ions, but rather not on the EUV flux. Under extreme solar wind conditions, Masunaga et al (2017), therefore, deduce, sputtering might even be reduced due to an increase of O + reflection into the solar wind.…”
Section: Non-thermal Escape Processes Over the Last ~4 Gyrmentioning
confidence: 98%